1987
DOI: 10.1007/bf01849247
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to human seminal plasma inhibin cause sperm agglutination and impairment of cervical mucus penetration and sperm-egg attachment

Abstract: Inhibin isolated from human seminal plasma which has 94 amino acids has been shown to be structurally similar to a sperm coating antigen of prostatic origin. Specific antibodies generated against this peptide caused agglutination of human sperm. Using FITC-labeled antibody, antigen was localized on the post-acrosomal head region of sperm. Antiserum to inhibin could also impair the penetration of human spermatozoa into cervical mucus. After 10 and 30 minutes, the depth and density of penetration as well as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

1990
1990
2009
2009

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…In addition, As hSPI also caused impairment of spermatogenesis, which ultimately resulted in interference of fertility. This supports our earlier in vitro results; we observed that As hSPI caused agglutination of ejaculated human spermatozoa and prevented spermatozoa from penetrating cervical mucus and inhibited sperm+gg interaction (Bandivdekar et al, 1987). An increase in seminal vesicle weight after 8 weeks of treatment was seen, which could possibly be due to transient change in androgen levels.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, As hSPI also caused impairment of spermatogenesis, which ultimately resulted in interference of fertility. This supports our earlier in vitro results; we observed that As hSPI caused agglutination of ejaculated human spermatozoa and prevented spermatozoa from penetrating cervical mucus and inhibited sperm+gg interaction (Bandivdekar et al, 1987). An increase in seminal vesicle weight after 8 weeks of treatment was seen, which could possibly be due to transient change in androgen levels.…”
Section: Discussionsupporting
confidence: 91%
“…Attempts have been made to isolate and purify biochemically different antigens from human sperm, seminal plasma, and testes and to investigate their immunologic effect on reproduction in female animals (reviewed by Naz, 1988). hSPI has been demonstrated to be a sperm-coating antigen (Johansson et al, 1984;Bandivdekar et al, 1987Bandivdekar et al, , 1988. The data obtained in the present study demonstrate for the first time the in vitro effect of As hSPI on rat epididymal sperm agglutination.…”
Section: Discussionmentioning
confidence: 99%
“…Estimation of DSP was calculated as described earlier (Gopalkrishnan et al, 1987). Estimation of DSP was calculated as described earlier (Gopalkrishnan et al, 1987).…”
Section: Daily Sperm Production (Dsp)mentioning
confidence: 99%
“…Tubules measuring 1-2 mm length were dissected, fixed, processed and embedded in araldite. Estimation of DSP was calculated as described earlier (Gopalkrishnan et al, 1987).…”
Section: Daily Sperm Production (Dsp)mentioning
confidence: 99%
See 1 more Smart Citation